The Distribution of Ultrahigh-energy Cosmic Rays along the Supergalactic Plane Measured at the Pierre Auger Observatory - A. Abdul Halim; P. Abreu; M. Aglietta; I. Allekotte; K. Almeida Cheminant; A. Almela; R. Aloisio; J. Alvarez-Muñiz; J. Ammerman Yebra; G.A. Anastasi; L. Anchordoqui; B. Andrada; et al. (The Astrophysical Journal)
Ultrahigh-energy cosmic rays are known to be mainly of extragalactic origin, and their propagation is limited by energy losses, so their arrival directions are expected to correlate with the large-scale structure of the local Universe. In this work, we investigate the possible presence of intermediate-scale excesses in the flux of the most energetic cosmic rays from the direction of the supergalactic plane region using events with energies above 20 EeV recorded with the surface detector array of the Pierre Auger Observatory up to 2022 December 31, with a total exposure of 135,000 km ^2 sr yr. The strongest indication for an excess that we find, with a posttrial significance of 3.1 σ , is in the Centaurus region, as in our previous reports, and it extends down to lower energies than previously studied. We do not find any strong hints of excesses from any other region of the supergalactic plane at the same angular scale. In particular, our results do not confirm the reports by the Telescope Array Collaboration of excesses from two regions in the Northern Hemisphere at the edge of the field of view of the Pierre Auger Observatory. With a comparable integrated exposure over these regions, our results there are in good agreement with the expectations from an isotropic distribution.